2008
DOI: 10.1210/jc.2008-0791
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vertebral Fractures in Men with Acromegaly

Abstract: This study reports for the first time a high prevalence of osteoporotic vertebral fractures in an unselected acromegalic male population generally considered at low risk of osteoporosis, suggesting that complicated osteoporosis is an important comorbidity of acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
86
2
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 44 publications
18
86
2
10
Order By: Relevance
“…It is therefore to be expected that disease control in acromegaly will be followed by a decrease in bone turnover and a filling of the remodeling space followed by a relative increase in BMD (11,27), as seen in other endocrine disorders with coupled bone remodeling, following treatment (37,38). The decrease in TBS following treatment in this study, despite the increase in BMD, reflects that the two measures describe different properties of bone, especially in other conditions than postmenopausal osteoporosis (4), but are in alignment with the observed high incidence and prevalence of vertebral fractures seen in acromegaly (5,31,32,33,34).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…It is therefore to be expected that disease control in acromegaly will be followed by a decrease in bone turnover and a filling of the remodeling space followed by a relative increase in BMD (11,27), as seen in other endocrine disorders with coupled bone remodeling, following treatment (37,38). The decrease in TBS following treatment in this study, despite the increase in BMD, reflects that the two measures describe different properties of bone, especially in other conditions than postmenopausal osteoporosis (4), but are in alignment with the observed high incidence and prevalence of vertebral fractures seen in acromegaly (5,31,32,33,34).…”
Section: Discussionsupporting
confidence: 72%
“…Recently, several studies have shown a marked increase in vertebral fracture prevalence and incidence for both sexes in acromegaly (5,31,32,33,34), related to the duration of disease activity and gonadal status among others. These observations underscore the complexity of a chronic and devastating disease as acromegaly, for bone as a target organ with fracture as the ultimate end point (2).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Bonadonna et al (15) found that in postmenopausal women with active acromegaly, the risk for VFs was high even in the presence of normal BMD, but that VFs were always associated with low BMD in controlled disease. The same group also demonstrated an increase in VF risk in men with acromegaly, especially in those with hypogonadism, irrespective of BMD (16). To date, the prevalence of fractures in relation with BMD has not been assessed in acromegalic patients after long-term biochemical control.…”
Section: Introductionmentioning
confidence: 91%
“…New techniques are needed to measure bone and joint integrity to assess better the effects of acromegaly treatment (MQ). [45][46][47][48] Different medications for acromegaly have different effects on glucose metabolism. SRLs might have a negative influence on glucose metabolism, but generally with marginal clinical relevance and most frequently in patients who do not have biochemical control of the disease.…”
Section: Comorbiditiesmentioning
confidence: 99%